2017
DOI: 10.1017/aaq.2017.40
|View full text |Cite
|
Sign up to set email alerts
|

Use and Multifactorial Reconciliation of Uniface Reduction Measures: A Pilot Study at the Nobles Pond Paleoindian Site

Abstract: How much stone tools are reduced and their form changed from first use to discard bears upon issues such as typological integrity, curation rate, and effects of occupation span. But degree of reduction depends partly upon the measures used to gauge it. Most studies involve single indices that gauge reduction in different ways or at different scales, so results are difficult to compare between studies. In this pilot study, we compare four allometric reduction measures—one each based on length, length:thickness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…The EPA-PD model often performs less well when applied to less controlled experimental replication assemblages and archeological assemblages. Although several studies have attempted to improve the EPA-PD model by adding other attributes such as platform width, platform area, and platform shape (Dibble 1997;Davis and Shea 1998;Shott et al 2000;Clarkson and Hiscock 2011;Lin et al 2013;Dogandžić et al 2015;Shott and Seeman 2017;Režek et al 2018;McPherron et al 2020), the ability of the model and its variants to accurately predict the original flake size is still limited. In their paper on the topic, Dibble and Rezek (2009) found that exterior platform angle, platform depth, and angle of blow all influenced flake mass, yet the angle of blow was mostly dropped from subsequent presentations of the model because the parameter could not be measured on the flakes themselves (see also Shott and Seeman 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The EPA-PD model often performs less well when applied to less controlled experimental replication assemblages and archeological assemblages. Although several studies have attempted to improve the EPA-PD model by adding other attributes such as platform width, platform area, and platform shape (Dibble 1997;Davis and Shea 1998;Shott et al 2000;Clarkson and Hiscock 2011;Lin et al 2013;Dogandžić et al 2015;Shott and Seeman 2017;Režek et al 2018;McPherron et al 2020), the ability of the model and its variants to accurately predict the original flake size is still limited. In their paper on the topic, Dibble and Rezek (2009) found that exterior platform angle, platform depth, and angle of blow all influenced flake mass, yet the angle of blow was mostly dropped from subsequent presentations of the model because the parameter could not be measured on the flakes themselves (see also Shott and Seeman 2017).…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous geometric measures for unifacial tools (e.g., Shott and Seeman 2017:729–731). For points, Hoffman proposed an allometric measure: a ratio of point length to blade edge-angle that captures “a dimension or scale of variability that can be used .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, different ranges of the Weibull shape parameter β implicate different failure scenarios. When 1 < β < 2, failure rate increases at a decreasing rate consistent with early wear-out failure, when β = 2 failure increases at a constant rate, and when β >2 failure increases at increasing rate (e.g., Douglass et al 2018; Morales 2016; Shott and Seeman 2017:732). Similarly, reduction distributions can distinguish between, for instance, competing scenarios of Folsom hunting practices by linking the duration of point use—and, by extension, distributions themselves—to different assumptions about group size and hunting rates (Hunzicker 2005:55–60).…”
Section: Allometry and Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human death-age distributions must be inferred from age-related osteological changes. Stone tool use-life distributions can be inferred from degree or pattern of reduction (Douglass et al 2018; Morales 2016; Shott and Seeman 2017). Until the relationship between vessel age and wear develops beyond its promising start (Skibo 1992), ceramic use-life distributions remain elusive except in ethnoarchaeological context.…”
Section: Defining Use Lifementioning
confidence: 99%